Synthesis of hyaluronated poly(exo-7-oxabicyclo[2.2.1]hept-5-en-2,3-dicarboxylic anhydride) brushes via a combination of surface-initiated ring-opening metathesis polymerization and thiol-ene click reaction - EROĞLU, MEHMET SAYIP (SPRINGER INTERNATIONAL PUBLISHING AG, 2021)
Well-defined hyaluronated poly(exo-7-oxabicyclo[2.2.1]hept-5-en-2,3-dicarboxylic anhydride) [poly(EHDA)-HA] brushes on the hydroxyl-terminated silicon (Si-OH) surface were prepared through the combination of surface-initiated ring-opening metathesis polymerization (ROMP) and thiol-ene click reaction. This process was realized in four successive steps: (i) formation of self-assembled monolayer of (3-aminopropyl) triethoxysilane on the Si-OH surface (Si-APTES), (ii) bonding of EHDA monomer to the Si-APTES surface, (iii) synthesis of poly(EHDA) brushes via surface-initiated ROMP and (iv) coupling of thiolated hyaluronic acid (Th-HA) to poly(EHDA) chains via thiol-ene click reaction. Surface wettability, surface morphology and chemical compositions of poly(EHDA)-HA brushes were characterized by contact angle measurements, atomic force, microscopy and X-ray photoelectron spectroscopy, respectively. Grafting density (sigma, chains nm(-2)) and average distance between grafting points (D, nm) of the poly(EHDA) brushes were measured to be 0.50 chains nm(-2) and 1.65 nm, independent of the [catalyst]/[monomer] ratios, which indicated that high grafting was created on the silicon substrate. However, low amounts of HA molecules were bonded to poly(EHDA) chains due to the high volume of Th-HA chains creating some steric hindrances. Biocompatible property of the poly(EHDA)-HA brushes are useful candidate for making advanced biological devices to control the behavior of biomolecules on surfaces.
Keywords: Exo-7-oxabicyclo[2.2.1]hept-5-en-2,3-3-dicarboxylic anhydride; Surface-initiated ring-opening metathesis polymerization (ROMP); Thiol-ene click reaction; Grafting density; TRANSFER RADICAL POLYMERIZATION; HYDROGEN-TERMINATED SILICON; ISOPROPYLACRYLAMIDE BRUSHES; MICHAEL ADDITION; WAFER; SUBSTRATE; FUNCTIONALIZATION; NANOPARTICLES; POLYMERS; GLYCOL)